RENCANA ANGGARAN BIAYA PADA PEMBANGUNAN PUSKESMAS DENGAN FASILITAS RAMAH LINGKUNGAN DI KELURAHAN TALANG KELAPA - Sidiq, Abdi Rachman; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Preparing a Budget Plan (RAB) is to calculate the costs required for a building and with these costs the building can be realized as planned. Considering the size and breadth of buildings for which costs must be calculated, knowledge of matters related to cost calculations is very necessary. There are requirements that must be met to prepare a budget plan, namely building construction drawings, building material prices and labor wages. Research on the budget plan was carried out on the Community Health Center Development Project with environmentally friendly facilities in Talang Kelapa Village, Alang - Alang Lebar District, Palembang City, South Sumatra Province by taking the unit price of materials in South Sumatra Province, From the results of this research, the planning for the construction of the Talang Kelapa Community Health Center building has a planned budget of IDR 938,628,000.00 (nine hundred thirty-eight million six hundred and twenty-eight thousand rupiah).Keywords : Cost Budget Plan, Community Health Center, Environmentally Friendly